Investigating Relationship between EVA and MVA of Selected Construction Companies in Malaysia - Panigrahi, Shrikant; Yuserrie, Zainuddin; Noor Azlinna, Azizan (theijbm.com, 2014)
There has always been high pressure on the companies to provide good performance in relation to increase wealth for shareholders. Shareholders in order to know the company’s performance rely on economic measures like Market value added (MVA). According to Stewert (1991) MVA is proxied by EVA and many of the studies found it evident similar to Stewert. Thus this paper examines the relationship between Economic Value Added (EVA) and Market Value Added (MVA) for the selected construction companies listed in Bursa Malaysia. Very few studies in Malaysia attempted to focus on the importance of economic measurement tools like EVA and MVA and their relationship. EVA measures the profitability of the companies considering cost of capital in the calculation.Thus the performance of the selected construction companies is identified based on the mean value of EVA and MVA for the periof of 11 years from 2002-2003 to 2012-2013). Thus this study makes an endeavor to fill this gap.The final result found that there is negative relationship between EVA and MVA. The negative relationship between EVA and MVA evidenced that the ability of using the capital by managers are adverse.